Experimental assessment of the performance and emissions of a spark-ignition engine using waste-derived biofuels as additives - Costa, Joaquim (2021)
The use of biofuels for spark ignition engines is proposed to diversify fuel sources and reduce fossil fuel consumption, optimize engine performance, and reduce pollutant emissions. Additionally, when these biofuels are produced from low-grade wastes, they constitute valorisation pathways for these otherwise unprofitable wastes. In this study, ethanol and pyrolysis biogasoline made from low-grade wastes were evaluated as additives for commercial gasoline (RON95, RON98) in tests performed in a spark ignition engine. Binary fuel mixtures of ethanol + gasoline or biogasoline + gasoline with biofuel incorporation of 2% (w/w) to 10% (w/w) were evaluated and compared with ternary fuel mixtures of ethanol + biogasoline + gasoline with biofuel incorporation rates from 1% (w/w) to 5% (w/w). The fuel mix performance was assessed by determination of torque and power, fuel consumption and efficiency, and emissions (HC, CO, and NOx). An electronic control unit (ECU) was used to regulate the air–fuel ratio/lambda and the ignition advance for maximum brake torque (MBT), wide-open throttle (WOT)), and two torque loads for different engine speeds representative of typical driving. The additive incorporation up to 10% often improved efficiency and lowered emissions such as CO and HC relative to both straight gasolines, but NOx increased with the addition of a blend.